CRITICAL-EMANCIPATORY JOURNALISM AND MARXIST ETHICS: the praxis of news against the order of capital - Bellan Rodrigues de Souza, Rafael (Brazilian journalism research, 2024)
ABSTRACT – The article defends the need for approximation between Adelmo Genro Filho’s proposal of critical-emancipatory journalism (2012) and the debates within Marxist ethics. Of a theoretical-conceptual nature, contributions are presented to, in the wake of the ontological foundations that support a Theory of Journalism, add to the necessarily collective, practical, and engaged development of news praxis. Ethical praxis as a guide for news praxis is, however, a confrontation and is only possible when taking a stand in the ongoing class struggle. This requires the return of the historical subject as an agent of the process of social metabolism, a mobilization that can count on the formative role of critical-emancipatory journalism, but which also depends on a broad renewed movement that places another form of collective life on the agenda. RESUMO – O artigo defende a necessidade de aproximação entre a proposta de jornalismo crítico-emancipatório de Adelmo Genro Filho (2012) e os debates no interior da ética marxista. De natureza teórico-conceitual, são apresentados aportes para, na esteira dos fundamentos ontológicos que sustentam uma Teoria do Jornalismo, contribuir para o desenvolvimento, necessariamente coletivo, prático e engajado, da práxis noticiosa. A práxis ética como guia da práxis noticiosa colocam-se, não obstante, como enfrentamento e só são possíveis ao se assumir um lugar na luta de classes em andamento. Isso exige o retorno do sujeito histórico como agente do processo de metabolismo social, mobilização que pode contar com o papel formador do jornalismo crítico-emancipatório, mas que depende também de um amplo movimento renovado que coloque na ordem do dia outra forma de vida coletiva. RESUMEN – El artículo defiende la necesidad de aproximación entre la propuesta de periodismo crítico-emancipador de Adelmo Genro Filho (2012) y los debates en el seno de la ética marxista. De carácter teórico-conceptual, se presentan aportes para a raíz de los fundamentos ontológicos que sustentan una Teoría del Periodismo, contribuir al desarrollo necesariamente colectivo, práctico y comprometido de la praxis informativa. La praxis ética como guía para la praxis noticiosa es, sin embargo, una confrontación y sólo es posible cuando toma un lugar en la lucha de clases en curso. Esto requiere el retorno del sujeto histórico como agente del proceso de metabolismo social, una movilización que puede contar con el papel formador del periodismo crítico-emancipador, pero que también depende de un amplio movimiento renovador que pone en juego otra forma de vida colectiva. la agenda.